RELEVANSI PROGRAM MAGANG TERHADAP PENGEMBANGAN KEPRIBADIAN MAHASISWA STKIP WIDYA YUWANA - Chrisnanto, Benediktus Ferry Patria (CREDENDUM: Jurnal Pendidikan Agama, 2019)
The internship program is one of the integrative components of the overall education program for catechist candidates and prospective Catholic religious teachers at STKIP Widya Yuwana. This program provides students with new experiences related to the working world they will face. Through the internship program, students are able to develop their personality. Two supporting factors in the development of students' personality are the internship and community service, which reflect the learning process as well as job opportunities in real-world situations. The issues addressed in this research are: What is an internship program? What is personality development? What is the relevance of the internship program to personality development according to STKIP Widya Yuwana students? Based on these issues, the aim of this study is to determine how far STKIP Widya Yuwana students are able to develop their personalities through internship programs. Respondents for this study were selected using a random sampling approach. The results of the study indicate that students understand the internship program and are able to develop their personalities, as seen from the data obtained.